NLRP3 inflammasome as prognostic factor and therapeutic target in primary progressive multiple sclerosis patients - Malhotra, Sunny; Costa, Carme; Eixarch, Herena; Keller, Christian W; Lukas Amman, Lukas; Martínez-Banaclocha, Helios; Midaglia, Luciana; Sarró, Eduard; Isabel Machín-Díaz, Isabel; M Villar, Luisa; Triviño, Juan Carlos; Oliver-Martos, Begoña; et al. (Oxford Academic, 2020)
Primary progressive multiple sclerosis is a poorly understood disease entity with no specific prognostic biomarkers and scarce therapeutic options. We aimed to identify disease activity biomarkers in multiple sclerosis by performing an RNA sequencing approach in peripheral blood mononuclear cells from a discovery cohort of 44 untreated patients with multiple sclerosis belonging to different clinical forms and activity phases of the disease, and 12 healthy control subjects. A validation cohort of 58 patients with multiple sclerosis and 26 healthy control subjects was included in the study to replicate the RNA sequencing findings. The RNA sequencing revealed an interleukin 1 beta (IL1B) signature in patients with primary progressive multiple sclerosis. Subsequent immunophenotyping pointed to blood monocytes as responsible for the IL1B signature observed in this group of patients. Functional experiments at baseline measuring apoptosis-associated speck-like protein containing a CARD (ASC) speck formation showed that the NOD-leucine rich repeat and pyrin containing protein 3 (NLRP3) inflammasome was overactive in monocytes from patients with primary progressive multiple sclerosis, and canonical NLRP3 inflammasome activation with a combination of ATP plus lipopolysaccharide was associated with increased IL1B production in this group of patients.
Keywords: Esclerosis múltiple; multiple sclerosis; biomarkers; therapeutic target; NLRP3 inflammasome; prognostic factor